Factors affecting cotton supply at the farm level in Metema District of Ethiopia - Bosena, T.; Bekabil, F.; Gebremedhin, Berhanu; Hoekstra, Dirk (2011)
Current available records show that Ethiopia is receiving negligible benefits from its cotton and textile products export partly on account of low production at the farm level. Our objective was to study factors responsible for the low production. The factors affecting farm level marketable supply of cotton were analyzed using Robust OLS regression analysis. Results showed that size of land allocated for cotton, productivity per hectare and access to credit were significant factors affecting farm level marketable cotton supply. Based on the study, policy interventions required to increase the supply of cotton were suggested